Severe/uncontrolled asthma and overall survival in atopic patients with eosinophilic granulomatosis with polyangiitis. (September 2018) - Berti, Alvise; Volcheck, Gerald W.; Cornec, Divi; Smyth, Robert J.; Specks, Ulrich; Keogh, Karina A.
Abstract: Background: Although asthma, rhinitis/rhinosinusitis and peripheral eosinophilia are present in virtually all patients with eosinophilic granulomatosis with polyangiitis (EGPA), the role of atopy in these patients is not well defined. Objective: To clarify the role of atopy in patients affected with EGPA. Methods: Clinical, laboratory and standard spirometry data have been abstracted from medical records. Only patients who underwent skin and/or specific IgE testing for common aeroallergens before the vasculitic phase were included. Results: Overall, 33.5% (63) of our patients underwent skin and/or specific IgE testing to aeroallergens. Atopy related to aeroallergens was confirmed in 22.3% (two-third of those tested), and was associated with more severe/uncontrolled asthma (p < 0.001), including a greater use of oral glucocorticoids for respiratory manifestations the year before the diagnosis of EGPA (p = 0.013). Atopic patients with EGPA had higher total serum IgE levels and less renal disease at EGPA diagnosis compared to non-atopic patients (p < 0.05). Among atopic patients, the majority had multiple sensitizations (76%); dust mite and grass pollen were the most common respiratory allergens identified. The number of allergens did not correlate with peripheral eosinophilia, total serum IgE, ESR, or measures of airway obstruction (p > 0.05 in all cases). The presence of atopy increased the risk of severe/uncontrolled asthma, but not the risk of severe vasculitis (Five Factor Score≥1). Atopic patients had a better overall survival (p = 0.027). Conclusion: In EGPA, atopy is associated with better prognosis and more severe/uncontrolled asthma manifestations in the year before the development of vasculitis, but not with more severe vasculitis at presentation. Highlights: What is already known about this topic? Asthma is present in virtually all patients with eosinophilic granulomatosis with polyangiitis (EGPA). Atopy has been reported in less than one-third of these patients and it may trigger exacerbations of asthma. The clinical role of atopy in EGPA patients is poorly understood. What does this article add to our knowledge? The presence of atopy increases the risk of severe/uncontrolled asthma in EGPA, potentially representing an under-recognized risk factor of asthma severity in these patients. Nevertheless, atopic patients with EGPA have a better overall survival, compared to the non-atopic ones. How does this study impact current management guidelines? A positive history of atopy, an asthma risk factor rarely investigated by clinicians in EGPA patients, may identify a subset of disease with worse asthma control and potentially better survival. Avoidance of aeroallergens and optimal allergy management should be considered in patients with EGPA.